Need Analysis of an English for Specific Purposes (ESP) Course for Indonesian Vocational Tertiary Students - Sitio, Ihsan Tanama; Hadiani, Dini; Permata, Nia Nuryanti; Latipah, Yeni (Institut Agama Islam Negeri Kudus, 2026)
The expanding use of English as a lingua franca for occupational, commercial, educational and industrial purposes has resulted in the global need for English for Specific Purposes (ESP) instruction in the English language teaching curriculum, especially in Indonesian context. However, most of the ESP courses offered are unable to address the students’ specific needs. Hence, this study investigates the role of needs analysis in ESP courses in vocational tertiary education level before designing any English Language Teaching curriculum in Indonesian context. Different yet interrelated sources of data collection including a set of closed-ended questionnaires, semi-structured interviews and classroom observation protocol were used to collect the relevant data. A total of 85 second-year students from a state polytechnic in Bandung, West Java, participated in this study. The results reveal that although knowledge of the four English language skills was figured out to be important for the students for being successful in both academic (educational) and professional (working) contexts, proficiency in speaking and reading was deemed to be of vital importance. The fulfillment of their academic targets, preparation for a better future, and becoming global citizens are the three perceived overarching reasons for the students to learn English. Accordingly, although students’ individual needs are basically subjective and unstable across contexts, this study’s findings can serve as a possible aid to decision-making in the contexts linking English language learning in vocational tertiary education to the broader professional world.